Unraveling resilience amidst degradation: Recurring loss of freshwater marshes in the Paraná River Delta, Argentina - Aquino, Diego Sebastián (2024)
Wetland ecosystems have experienced several ecological and hydrological impacts in recent decades determined by human activities and natural disturbances. The Lower Delta of the Paraná River, one of the most important wetland ecosystems of South America, has seen significant losses in both the structural and functional components of wetland vegetation. These losses promoted not only a widespread conversion of freshwater marshes into grasslands between 1997 and 2013, but also a decline in ecosystem functional diversity between 2001 and 2015. These processes manifested as abrupt shifts in long-term vegetation dynamics, a distorted, transient, spatially heterogeneous relationship with the hydrologic regime, and altered plant communities. However, recent field observations (2015–2023) have partially challenged previous findings and assumptions. Thus, we ask whether previously observed wetland losses are part of a long-term periodic process, rather than a permanent change. To address this question, we studied land use and land cover conversions through an object-based supervised classification of yearly Landsat composites between 1985 and 2023, trained on 935 ground-truth points. To study the spatial and temporal patterns of wetland gain and loss, we implemented an Intensity Analysis (IA), as well as analyses that capture frequency-specific variations and identify significant shifts in linear trends. We produced a total of 39 land cover maps. The IA revealed non-stationarity at all levels of analysis: interval, category, and transition. The study area exhibited resilient patterns through significant and increasingly short-term, periodic dynamics guiding the gain and loss of freshwater marshes. On the opposite, long-term, negative trends depicted an absolute, sustained loss. These contrasting patterns suggest that despite experiencing absolute loss and degradation, wetland ecosystems thrive by exhibiting transient recovery or adaptation mechanisms. Our study unraveled the complexity of wetland ecosystem dynamics, emphasizing how resilience and degradation interplay in the context of land use intensification.